A history of the Jewish people in the time of Jesus Christ - Schürer, Emil (Scribner, 1891)
-Div.1. Political history of Palestine, from B.C.175 to A.D.135. -Div. 2. The internal condition of Palestine, and of the Jewish people, in the time of Jesus Christ.